Biodegradation of polyethylene mulching films by a co-culture of Acinetobacter sp. strain NyZ450 and Bacillus sp. strain NyZ451 isolated from Tenebrio molitor larvae - Yin, Chao-Fan; Xu, Ying; Zhou, Ning-Yi (International biodeterioration & biodegradation, 2020)
Microbial degradation of polyethylene (PE) mulching films has attracted much attention, but to date its relatively rapid biodegradation was limited. Here, a consortium of two bacterial isolates, Acinetobacter sp. strain NyZ450 and Bacillus sp. strain NyZ451 from the gut of PE-feeding Tenebrio molitor larvae (mealworms), was suggested to utilize PE, although each strain had no such ability alone. This consortium removed approximately 18% of PE film after 30 days at 23 °C. High-temperature gel permeation chromatography analysis indicated that the number-, weight-, and size-averaged molecular weights of PE were decreased by 14%, 24% and 21% from their respective initial values of 27,494 Da, 179,374 Da and 697,487 Da after a 20-day incubation with this consortium. Under scanning electron microscope, a biofilm formed by these strains was also observed on the film's surface. Fourier transform infrared spectroscopy analysis indicated that the films incubated with these two strains or either of them were all oxidized compared with the control without inoculation. Plate colony counting and electron microscopic observation showed that strain NyZ450 was predominant in the co-culture. This study enriched microbial resources for PE degradation and provided an example for the interaction of two bacterial strains for enhanced PE degradation. [Display omitted] •A consortium of two bacteria from the Tenebrio molitor larvae gut degrades PE.•The co-culture reduced 18% mass of PE mulching films in 30 days.•The two isolates form a tight biofilm on the PE mulching film surface.•PE undergoes oxidation after being treated with two strains.•Acinetobacter sp. strain NyZ450 is predominant in the consortium.